Utilization of fauna resources for therapeutic purposes as a barrier to species justice advocacy in Nigeria - Adebowale, Taiwo Kabiru; Ijose, Opemipo Alaba; Ibiyomi, Bolade Bosede; Akintunde, Oluyinka O.; Oduntan, Oladapo O.; Osunsina, Israel Oluyinka Oloyede; Shobowale, Aishah Adeola (Frontiers in Conservation Science, 2025)
Efforts to reduce the irrational exploitation of wildlife, aimed at achieving species justice, continue to be challenged by the persistent demand for animal parts and derivatives in formulating alternative medicines in certain regions of Nigeria. This study focuses on the Kuto, Iberekodo, Itoku, and Lafenwa markets in Ogun State, known for the many traditional medical practitioners relying on these markets for alternative remedies. Data were collected through a semi-structured questionnaire distributed randomly to 165 traditional medicinal vendors. The survey identified 49 animal species of conservation concern; these are categorized as follows: two molluscs, two amphibians, two insects, five fish, eight reptiles, nine birds, and 21 mammals. Various animal parts are traded for spiritual empowerment and disease treatment in these markets. This trade negatively impacts conservation efforts and undermines the collective endeavors of all stakeholders to promote species justice in Nigeria.